TA’WID AND GHARAMAH IN INDONESIA’S MURABAHA FINANCING: AN ISLAMIC LAW-AND-ECONOMICS ANALYSIS OF INCENTIVES AND CONSUMER PROTECTION - Mega Mustika; Ridwan Malik; Hasanuddin; Mohd Aizul Yaakob (Referensi Islamika: Jurnal Studi Islam, 2026)
This study examines why late-payment charges in Islamic banking remain contested, particularly at the boundary between legitimate cost recovery and prohibited time-based gain. It evaluates how taʿwīḍ (compensation) and gharāmah (penalty) are designed and whether they genuinely enhance consumer protection or risk operating as hidden pricing in Indonesian murābaḥah financing. A mixed normative–qualitative approach is employed by triangulating doctrinal analysis of Indonesian Sharia banking regulations and DSN–MUI fatwas, document review of contract templates and internal procedures, and semi-structured interviews with financing officers, Sharia Supervisory Board members, and affected customers. An Islamic law-and-economics framework is applied to assess incentive compatibility under information asymmetry and default risk. The study finds that taʿwīḍ is justifiable only when linked to verifiable incremental costs with clear evidentiary standards and ex ante disclosure. Gharāmah is effective as a deterrent only when revenue-neutral, transparently allocated, and properly governed. Key vulnerabilities include ambiguous contract clauses, weak disclosure mechanisms, and fragmented accountability structures. The study is limited to Indonesian murābaḥah practices and relies on qualitative data, which may affect generalizability across jurisdictions and contract types. This article offers a compliance-by-design framework separating taʿwīḍ and gharāmah in drafting and accounting, introducing cost-verification protocols, audit trails, and transparent dispute mechanisms to align Sharia compliance with modern consumer protection standards.